Steps on Pt stereodynamically filter sticking of O(2) - Cao, Kun (Proc Natl Acad Sci U S A, 2019)
Low coordinated sites on catalytic surfaces often enhance reactivity, but the underlying dynamical processes are poorly understood. Using two independent approaches, we investigate the reactivity of O(2) impinging onto platinum and resolve how step edges on (111) terraces enhance sticking. At low incident energy, the linear dependence on step density, independence of step type, and insensitivity to O(2)’s molecular alignment show that trapping into a physisorbed state precedes molecular chemisorption and dissociation. At higher impact energies, direct molecular chemisorption occurs in parallel on steps and terraces. While terraces are insensitive to alignment of the molecule within the (111) plane, steps favor molecules impacting with their internuclear axis parallel to the edge. Stereodynamical filtering thus controls sticking and dissociation of O(2) on Pt with a twofold role of steps.